pH and microbial community determine the denitrifying activity in the presence of nitrate-containing radioactive waste - Mijnendonckx, Kristel; Bleyen, Nele; Van Gompel, Axel; Coninx, Ilse; Leys, Natalie (Frontiers in Microbiology, 2022)
An important fraction of the currently stored volume of long-lived intermediate-level radioactive waste in Belgium contains large amounts of NaNO3 homogeneously dispersed in a hard bituminous matrix. Geological disposal of this waste form in a water-saturated sedimentary formation such as Boom Clay will result in the leaching of high concentrations of NaNO3, which could cause a geochemical perturbation of the surrounding clay, possibly affecting some of the favorable characteristics of the host formation. In addition, hyper-alkaline conditions are expected for thousands of years, imposed by the cementitious materials used as backfill material. Microbial nitrate reduction is a well-known process and can result in the accumulation of nitrite or nitrogenous gases. This could lead to the oxidation of redox-active Boom Clay components, which could (locally) decrease the reducing capacity of the clay formation. Here, we compared nitrate reduction processes between two microbial communities at different pH related to a geological repository environment and in the presence of a nitrate-containing waste simulate during 1 year in batch experiments. We showed that the microbial community from in Boom Clay borehole water was able to carry out nitrate reduction in the presence of acetate at pH 10.5, although the maximum rate of 1.3 ± 0.2 mM NO3−/day was much lower compared to that observed at pH 9 (2.9 mM NO3−/day). However, microbial activity at pH 10.5 was likely limited by a phosphate shortage. This study further confirmed that the Harpur Hill sediment harbors a microbial community adapted to high pH conditions. It reduced twice as much nitrate at pH 10.5 compared to pH 9 and the maximum nitrate reduction rate was higher at pH 10.5 compared to that at pH 9, i.e., 3.4 ± 0.8 mM NO3−/day versus 2.2 ± 0.4 mM NO3−/day. Both communities were able to form biofilms on non-radioactive Eurobitum. However, for both microbial communities, pH 12.5 seems to be a limiting condition for microbial activity as no nitrate reduction nor biofilm was observed. Nevertheless, pH alone is not sufficient to eliminate microbial presence, but it can induce a significant shift in the microbial community composition and reduce its nitrate reducing activity. Furthermore, at the interface between the cementitious disposal gallery and the clay host rock, the pH will not be sufficiently high to inhibit microbial nitrate reduction.